The Influence of Creative Industries on the Russian Economy: Service, Hospitality, Advertising and Others - Levitskaia I. A., Konnov V. I., Domashina E. E., Emelianova V. A., Filimonov O. I., Miroshnikova T. K., Levchenko K. K., Levchenko T. P., Verna V. V., Ibragimov E. E., Radina O. I., Alekhina E. S., Volodina T. V. (The Influence of Creative Industries on the Russian Economy: Service, Hospitality, Advertising and Others, 2022)
the main problems of introducing mentoring at hospitality and tourism enterprises in the context of digital transformations are discussed in the chapter. The authors substantiate the relevance of the research, analyzes the prerequisites of digital transformations in the tourism industry, conducts a theoretical study of the content of mentoring using the following methods: abstract-logical and content analysis, classification, generalization, monographic method and method of system analysis. The data obtained made it possible to develop a structural and logical model for the introduction of mentoring at hospitality and tourism enterprises in the context of digital transformations.
Keywords: модель; наставничество; персонал; наставник; staff; model; mentor; mentoring; предприятия гостеприимства и туризма; программа наставничества; hospitality and tourism enterprises; mentoring program